Microbial Threshold Guidelines for UTI Diagnosis: A Scoping Systematic Review - Hilt EE; Parnell LK; Wang D; Stapleton AE; Lukacz ES (Dove Medical Press, 2023)
Evann E Hilt,1 Laura KS Parnell,2 Dakun Wang,3 Ann E Stapleton,4 Emily S Lukacz5 1Author affiliations Department of Laboratory Medicine and Pathology, M Health Fairview University of Minnesota Medical Center, Minneapolis, MN, USA; 2Author affiliations Department of Scientific Writing, Precision Consulting, Missouri City, TX, USA; 3Author affiliations Department of Writing, Stat4Ward, Pittsburgh, PA, USA; 4Author Affiliations Department of Medicine, University of Washington, Seattle, WA, USA; 5Author affiliations Department of Obstetrics, Gynecology & Reproductive Sciences, University of California San Diego, La Jolla, CA, USACorrespondence: Laura KS Parnell, Precision Consulting, 6522 Harbor Mist, Missouri City, TX, 77459, USA, Tel +1 281-208-3037, Email lksparnell@yahoo.comAbstract: Given the growing impact of antimicrobial resistance, improvements in diagnosis and treatment of the most common outpatient infection, urinary tract infection (UTI), are of great interest to stakeholders. Regulatory authorities have long accepted a microbial threshold of 105 CFU/mL as the standard for diagnosing UTI based on standard urine cultures. However, microbial thresholds considered clinically relevant remain in dispute. The aim of this systematic scoping review is to assess the evidence supporting a threshold of 105 CFU/mL, to review microbial threshold guidelines, and highlight knowledge gaps in the diagnosis of UTI. A total of 36 guidelines containing 144 recommendations were identified with 64% of guidelines (n = 23) and 58% of recommendations (n = 83) published in the last six years (2016- 2023). Recommendations have changed over time and across variables including the geographical location of the guideline, urine specimen collection method, patient sex, and category of UTI. Guidelines uniformly agreed with suprapubic needle specimen collection; however, there was no consensus for midstream collected urine samples. Guideline microbial thresholds for clinical UTI diagnosis were higher for women at average risk (105 CFU/mL) than for men (102 to 105 CFU/mL) and high-risk patients (102 to 104 CFU/mL). Guidelines relied heavily on 48 research articles from 20 author teams published between 1956 and 2019 and recommendations frequently cited 23 research articles by 15 author teams published between 1956 and 2013. Evidence supporting 105 CFU/mL threshold originated in the mid-1950s from 4 research articles, whereas 18 frequently cited peer-reviewed publications focused their research on the clinical relevance of lower thresholds (101 to < 105 CFU/mL). This review demonstrates a lack of consensus for urine culture microbial threshold recommendations for the clinical diagnosis of UTI. Guidelines are primarily based upon sparse and dated evidence. Additional research is needed to inform clinically meaningful diagnostic microbial thresholds in the diagnosis of UTI.Keywords: urinary tract infection, guideline, microbial, diagnostic threshold, uropathogen, scoping systematic review